Multidisciplinary Approach To Acute Mesenteric Ischemia – A Success Case - Nogueira, Oriana (2024)
Introduction: Acute Mesenteric Ischemia (AMI) is a surgical emergency that results from interruption of mesenteric vascular flow. With a multifactorial etiology, it is often associated with embolic occlusion of the superior mesenteric artery (SMA). Late diagnosis and patient co-morbidities usually lead to high surgical morbidity and mortality rates. Case Report: We describe a case of a 57-year-old man, admitted to the Emergency Department (ED) with acute abdominal pain and vomiting. After clinical examination and computerized tomography (CT) scan imaging the subject was diagnosed with mesenteric ischemia. The patient underwent emergent surgery, with a multidisciplinary approach including general surgery and vascular surgery teams. Conclusion: Early diagnosis associated with adequate resuscitation was essential in the patient’s prognosis.